Review: Integrative Coordination Abilities of Coaches in Wellness Types of Gymnastics (Baltic Journal of Sport and Health Sciences, 2015)
Background. The coordination development level influences the execution of any human activity, which is very important for the general perception of this activity and behavior in general. It is especially relevant for to coaches in wellness and sports gymnastics. The aim of the present study was the identification of the coordination skills of coaches of different types of gymnastics, which would improve the process of their professional training.Material and Methods. This review presents a synthesis of research conducted by the author. The following methods of theoretical research were used: abstract and axiomatic methods, analysis and synthesis, induction and deduction, idealization, comparison and generalization, and projecting.Results. The coaches’ training in different types of gymnastics includes the development of a wide range of professional skills: the tandem of communicative and motor skills that determine one type of complex coordination. The realization of complex coordination presupposes the participation of sensor systems (analyzer systems), which are visual, auditory, tactile, vestibular, and motor systems. The basic speech component of complex coordination in coaches’ activity/behavior determines his/her communicative orientation in the process of teaching. It is explained by the connection between the cultivation of complex coordination skills with the congenital and genetic, anatomical and physiological particularities of the human organism. We determined the coordination abilities, the formation of which contributes to the development of complex coordination skills.Conclusion. Development of integrative coordination abilities is an important part of professional activity of coaches of gymnastics, which requires such preparation.Keywords:  coordination, professional skills, coach, gymnastics, aerobics.